2003
DOI: 10.1186/1471-2148-3-18
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of bacterial and archaeal arsC gene sequences suggests an ancient, common origin for arsenate reductase

Abstract: Background: The ars gene system provides arsenic resistance for a variety of microorganisms and can be chromosomal or plasmid-borne. The arsC gene, which codes for an arsenate reductase is essential for arsenate resistance and transforms arsenate into arsenite, which is extruded from the cell. A survey of GenBank shows that arsC appears to be phylogenetically widespread both in organisms with known arsenic resistance and those organisms that have been sequenced as part of whole genome projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…The pervasive spread of As resistance genes in microbial lineages at the base of the tree of life (e.g., Gihring et al 2003; Jackson and Dugas 2003), suggests exposure to As in the deep geological past (Chen et al 2017; Tian and Luo 2017). This ancient interplay between life and As resulted in the biological innovation of resistance mechanisms whereby As(V) is reduced with unique cytoplasmic As(V) reductases to As(III), followed by extrusion via specific As(III) cell membrane protein transporters (Rosen 2002; Jackson and Dugas 2003; Cai et al 2009; Dziubinska-Maciaszczyk et al 2011; Rosen et al 2011; Slyemi and Bonnefoy 2012a, b; Zhu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pervasive spread of As resistance genes in microbial lineages at the base of the tree of life (e.g., Gihring et al 2003; Jackson and Dugas 2003), suggests exposure to As in the deep geological past (Chen et al 2017; Tian and Luo 2017). This ancient interplay between life and As resulted in the biological innovation of resistance mechanisms whereby As(V) is reduced with unique cytoplasmic As(V) reductases to As(III), followed by extrusion via specific As(III) cell membrane protein transporters (Rosen 2002; Jackson and Dugas 2003; Cai et al 2009; Dziubinska-Maciaszczyk et al 2011; Rosen et al 2011; Slyemi and Bonnefoy 2012a, b; Zhu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the challenge of As toxicity, a peculiar but polyphyletic group of microorganisms conserve energy from As, by respiring As(V) to As(III) and by oxidizing As(III) back to As(V) in a variety of marine and terrestrial habitats (e.g., Mukhopadhyay et al 2002; Smedley and Kinniburgh 2002; Oremland and Stolz 2003; Rosen 2002; Gihring et al 2003; Jackson and Dugas 2003; Oremland and Stolz 2003; Saltikov and Newman 2003; Malasarn et al 2004; Stauder et al 2005; Silver and Phung 2005; Quéméneur et al 2008; Cai et al 2009; Fu et al 2009; Henke et al 2009; Newman et al 2009; Qin et al 2009; Dyhrman and Haley 2011; Dziubinska-Maciaszczyk et al 2011; Rosen et al 2011; Sánchez-Riego et al 2014; Zhu et al 2014, 2017; Gilhooly et al 2014; Jiang et al 2014; Rascovan et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Although arsenic is most notorious as a poison threatening human health [1], recent studies suggest that arsenic species may have been involved in the ancestral taming of energy and played a crucial role in early stages in the development of life on Earth [2,3]. Further speculations involve this metalloid in the colonization of extraterrestrial environments containing high arsenic levels [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the detection of arsenic resistance genes (arsC) in our metagenomic assembly from Pohaku Vents represents an exciting opportunity to investigate arsenic detoxification in microbial mat communities at Lo 'ihi. This enzyme catalyzes the intracellular reduction of arsenate to arsenite, which is then extruded from the cell via an arsenite-specific protein pump (31,32). Meyer-Dombard et al found both arsC and zetaproteobacterial SSU rRNA gene sequences in vent fluids and slide colonization experiments in the arsenic-rich waters at shallow hydrothermal vents at Tutum Bay, Papua New Guinea (33).…”
mentioning
confidence: 99%